Workplace health promotion programs for older workers in Italy - Magnavita, Nicola; Capitanelli, Ilaria; Garbarino, Sergio; La Milia, Daniele Ignazio; Moscato, Umberto; Pira, Enrico; Poscia, Andrea; Ricciardi, Walter (La Medicina del Lavoro, 2017)
Background: Italy is the European country with the highest number of citizens over the age of sixty. In recent years, the unsustainability of the social security system has forced the Italian government to raise the retirement age and reduce the chances of early exit, thus sharply increasing the age of the workforce. Consequently, a significant proportion of older workers are currently obliged to do jobs that were designed for young people. Systematic health promotion intervention for older workers is therefore essential. Objectives: The European Pro Health 65+ project aims at selecting and validating best practices for successful/active aging. In this context we set out to review workplace health promotion projects carried out in Italy. Methods: To ascertain examples of workplace health promotion for older workers (WHPOW), we carried out a review of the scientific and grey literature together with a survey of companies. Results: We detected 102 WHPOW research studies conducted in conjunction with supranational organizations, public institutions, companies, social partners, NGOs and educational institutions. The main objectives of the WHPOW were to improve the work environment, the qualifications of older workers and attitudes towards the elderly, and, in many cases, also to improve work organization. Conclusions: The best way to promote effective WHPOW interventions is by disseminating awareness of best practices and correct methods of analysis. Our study suggests ways of enhancing WHPOW at both a national and European level.